A novel piezoelectric actuator with two operating modes. (April 2018) - Liu, Yingxiang; Shi, Shengjun; Yan, Jipeng; Chen, Weishan; Xu, Dongmei
A novel piezoelectric actuator with two operating modes is proposed and tested in this work, whose unique feature is that it has different mechanical output performances under two bending resonance frequencies. The proposed actuator is fabricated by bonded eight pieces of lead zirconate titanate ceramic plates on an aluminum alloy beam symmetrically. When the ceramic plates are excited by signals with resonance frequency of the first bending mode of the actuator, two bending vibrations will be superimposed to form elliptical movements on the two driving tips, which is the first operating mode. The other operating mode can be realized easily by changing the working frequency to the second bending mode of the actuator. These two operating modes are calculated and compared in detail. The prototype achieves a maximum no-load speed of 171 mm/s and maximum thrust force of 0.6 N using the first operating mode, whereas these two values are increased to be about 208 mm/s and 0.76 N under the second operating mode. The weight of the proposed piezoelectric actuator is about 17.7 g, and the maximum force weight ratio is tested to be about 42.9 N/kg.